Is Self-Compassion a Worthwhile Therapeutic Target for ICD-11 Complex PTSD (CPTSD)?. Issue 3 (2nd October 2018) - Karatzias, Thanos; Hyland, Philip; Bradley, Aoife; Fyvie, Claire; Logan, Katharine; Easton, Paula; Thomas, Jackie; Philips, Sarah; Bisson, Jonathan I.; Roberts, Neil P.; Cloitre, Marylene; Shevlin, Mark
Abstract : Background: Two 'sibling' disorders have been proposed for the fourthcoming 11th version of the International Classification of Diseases (ICD-11): post-traumatic stress disorder (PTSD) and complex PTSD (CPTSD). Examining psychological factors that may be associated with CPTSD, such as self-compassion, is an important first step in its treatment that can inform consideration of which problems are most salient and what interventions are most relevant. Aims: We set out to investigate the association between self-compassion and the two factors of CPTSD: the PTSD factor (re-experiencing, avoidance, sense of threat) and the Disturbances in Self-Organization (DSO) factor (affect dysregulation, negative self-concept and disturbances in relationships). We hypothesized that self-compassion subscales would be negatively associated with both PTSD and DSO symptom clusters. Method: A predominantly female, clinical sample ( n = 106) completed self-report scales to measure traumatic life events, ICD-11 CPTSD and self-compassion. Results: Significant negative associations were found between the CPTSD DSO clusters of symptoms and self-compassion subscales, but not for the PTSD ones. Specifically it was also found that self-judgement and common humanity significantly predicted hypoactive affect dysregulation whereas self-judgement and isolation significantly predicted negative self-concept. Conclusions: Our results indicate that self-compassion may be a useful treatment target for ICD-11 CPTSD, particularly for symptoms of negative self-concept and affect dysregulation. Future research is required to investigate the efficacy and acceptability of interventions that have implicit foundations on compassion.